A metal sulfide-based composite catalyst and its preparation method and application

By loading non-metallic atom-doped nickel sulfide nanosheets containing sulfur vacancy on the MXene substrate, the problems of insufficient active sites and low conductivity of transition metal sulfide catalysts are solved, and efficient hydrogen evolution reaction performance is achieved.

CN115287672BActive Publication Date: 2025-04-11HARBIN INST OF TECH SHENZHEN GRADUATE SCHOOL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210820706.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-13
Publication Date
2025-04-11
Estimated Expiration
2042-07-13

AI Technical Summary

Technical Problem

The transition metal sulfide catalyst with a lamellar structure in the existing transition metal sulfide catalyst has problems such as insufficient active sites, insufficient reactivity and low electron conductivity, which limits its performance in hydrogen evolution reaction.

Method used

The MXene substrate is loaded with non-metallic atomic doped nickel sulfide nanosheets, and the sulfur vacancy is introduced through non-metallic atomic doping, which enhances the ability to capture protons and improves the specific surface area and conductivity through MXene material.

Benefits of technology

The number of active sites, conductivity and reaction activity of the catalyst are significantly improved, the performance of hydrogen evolution reaction is enhanced, and the performance of the hydrogen evolution reaction is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115287672B_ABST
    Figure CN115287672B_ABST
Patent Text Reader

Abstract

The present invention discloses a metal sulfide-based composite catalyst and a preparation method and application thereof. The metal sulfide-based composite catalyst comprises a MXene substrate and a non-metal atom-doped nickel sulfide nanosheet containing sulfur vacancies loaded on the surface of the MXene substrate. The nickel sulfide nanosheet is doped with non-metal atoms to cause lattice distortion, thereby introducing sulfur vacancies to enhance the ability to capture protons and enhance the reaction activity. At the same time, the nickel sulfide nanosheet is doped with non-metal atoms to increase the number of active sites and improve the conductivity; the sulfur vacancies in the nickel sulfide nanosheet can be used as additional active sites for hydrogen evolution reaction, and at the same time, the electrons are positioned near the defects, which is conducive to the transfer of electrons to proton hydrogen, thereby greatly improving the catalytic performance. There is a synergistic coupling effect between the non-metal atom-doped nickel sulfide nanosheet and the MXene material, which can adjust the electronic structure of the intermediate in the catalytic hydrogen evolution reaction process, reduce its energy barrier, and improve the hydrogen evolution reaction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis, and in particular to a metal sulfide-based composite catalyst and a preparation method and application thereof. Background Art

[0002] Renewable energy such as solar energy, wind energy, and tidal energy are affected by many objective factors that are difficult to control stably (such as the inability to use solar energy on cloudy days, etc.), making them difficult to use in daily life. Hydrogen energy has the advantages of high calorific value and high environmental friendliness, and is one of the most promising energy sources in the future energy industry. The hydrogen evolution reaction (HER) is a safe and pollution-free method for producing hydrogen that complies with the sustainable development strategy. It plays a vital role in clean energy conversion and has become a major trend in the development of new energy in recent years.

[0003] For HER, the best catalyst is the precious metal Pt, but its large-scale application is restricted by its high price and production cost. Therefore, finding efficient, economical and stable electrode catalysts is the decisive means to popularize water electrolysis hydrogen production technology in the market.

[0004] Lamellar transition metal sulfides have a lamellar structure similar to graphene and belong to the hexagonal crystal system. They have the advantages of low price, sufficient raw materials, good corrosion resistance, and good catalytic performance. However, the electronic conductivity of lamellar transition metal sulfides is anisotropic, that is, the electron transfer on the nanosheet base is slow, and its conductivity still needs to be improved. In addition, lamellar transition metal sulfide catalysts also have the problems of insufficient active sites and insufficient reaction activity on the active sites, which greatly limits the HER performance of transition metal sulfide catalysts.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a metal sulfide-based metal sulfide-based composite catalyst and a preparation method and application thereof, aiming to solve the problems of insufficient active sites, insufficient reaction activity on the active sites and the need to improve the electrical conductivity of the existing transition metal sulfide catalysts with lamellar structures.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect of the present invention, a metal sulfide-based composite catalyst is provided, wherein the metal sulfide-based composite catalyst comprises a MXene substrate and nickel sulfide nanosheets doped with non-metal atoms containing sulfur vacancies and loaded on the surface of the MXene substrate.

[0009] Optionally, the non-metal atom is selected from one or more of N atom, B atom and F atom.

[0010] Optionally, the MXene substrate is selected from Mo 2 CT x Substrate, Ti 3 C 2 T x Substrate, Ti 2 CT x Base, Cr 2 CT x Base and V 2 CT x One or more of the substrates, wherein T represents a functional group and x represents the number of functional groups.

[0011] Optionally, the mass ratio of the MXene substrate to the nickel sulfide nanosheets doped with non-metal atoms containing sulfur vacancies is 1:(3-5).

[0012] The second aspect of the present invention provides a method for preparing the metal sulfide-based composite catalyst as described above, which comprises the steps of:

[0013] Adding MXene, nickel salt, urea, citric acid, and an ionic liquid containing non-metal atoms into water to obtain a mixed solution;

[0014] The mixed solution is reacted at a temperature of 120 to 160° C. for 8 to 16 hours;

[0015] The product obtained after the reaction is subjected to sulfidation treatment to obtain the metal sulfide-based composite catalyst.

[0016] Optionally, the nickel salt is selected from at least one of nickel nitrate, nickel chloride and nickel acetate.

[0017] Optionally, the ionic liquid containing non-metal atoms is selected from at least one of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-fluoropyridine tetrafluoroborate, and tri-n-butylphosphine tetrafluoroborate.

[0018] Optionally, the temperature of the vulcanization treatment is 450-550° C., and the time is 50-70 minutes.

[0019] Optionally, the step of subjecting the product obtained after the reaction to a sulfurization treatment specifically comprises:

[0020] The product obtained after the reaction and the sulfur powder are placed at different positions of the sintering furnace and heated respectively, and the product after the reaction is subjected to a sulfurization treatment.

[0021] The third aspect of the present invention provides a use of the metal sulfide-based composite catalyst as described above in an electrocatalytic hydrogen evolution reaction;

[0022] Alternatively, the present invention provides an application of the metal sulfide-based composite catalyst prepared by the preparation method as described above in an electrocatalytic hydrogen evolution reaction.

[0023] Beneficial effects: The metal sulfide-based composite catalyst of the present invention includes a MXene substrate and a nickel sulfide nanosheet doped with non-metallic atoms containing sulfur vacancies loaded on the surface of the MXene substrate. Nickel sulfide nanosheets have high stability and corrosion resistance, and have a d electronic structure similar to that of Pt, and can play an excellent catalytic performance in the hydrogen evolution reaction. The nickel sulfide nanosheets are doped with non-metallic atoms to cause lattice distortion, and then sulfur vacancies are introduced to enhance the ability to capture protons and enhance the reaction activity. At the same time, the nickel sulfide nanosheets are doped with non-metallic atoms to increase the number of active sites and improve the conductivity; the sulfur vacancies in the nickel sulfide nanosheets can serve as additional active sites for the hydrogen evolution reaction, and at the same time, the electrons are positioned near the defects (i.e., sulfur vacancies), which is conducive to the transfer of electrons to proton hydrogen, thereby greatly improving the catalytic performance. Since MXene materials have a two-dimensional layered structure and excellent metallic conductivity, the specific surface area and conductivity of the composite catalyst can be further improved by introducing MXene materials, accelerating the transmission of electrons, and there is a synergistic coupling effect between the nickel sulfide nanosheets doped with non-metallic atoms and the MXene materials, which can adjust the electronic structure of the intermediates in the catalytic hydrogen evolution reaction process, reduce its energy barrier, and improve the hydrogen evolution reaction performance. The metal sulfide-based composite catalyst provided by the present invention has abundant sulfur vacancies, a large electrochemically active specific surface area, more active sites, high double-layer capacitance, low Tafel slope, and excellent electrocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 (a) is Mo in Example 1 of the present invention 2 CT x (b) is the SEM image of NBF-Ni-LDH / Mo in Example 1 of the present invention. 2 CT x (c) is the SEM image of NBF-NiS / Mo in Example 1 of the present invention. 2 CT x SEM image of .

[0025] Figure 2 (a) is NBF-NiS / Mo in Example 1 of the present invention 2 CT x TEM image of NBF-NiS / Mo in Example 1 of the present invention. 2 CT x High-magnification TEM image of the crystal striations.

[0026] Figure 3 Mo in Example 1 of the present invention2 CT x and NBF-NiS / Mo 2 CT x XRD pattern of .

[0027] Figure 4 NBF-NiS / Mo in Example 1 of the present invention 2 CT x XPS spectra, where (a) is the 1s characteristic peak spectrum of B, (b) is the 1s characteristic peak spectrum of N, (c) is the 1s characteristic peak spectrum of F, (d) is the 3d characteristic peak spectrum of Mo, (e) is the 1s characteristic peak spectrum of C, (f) is the 2p characteristic peak spectrum of Ni, and (g) is the 2p characteristic peak spectrum of S.

[0028] Figure 5 (a) is NBF-NiS / Mo in Example 1 of the present invention 2 CT x Element content result diagram, (b) NBF-NiS / Mo in Example 1 of the present invention 2 CT x SEM images of the samples, (c) is the Ni element distribution map corresponding to the area in (b), (d) is the S element distribution map corresponding to the area in (b), (e) is the B element distribution map corresponding to the area in (b), (f) is the N element distribution map corresponding to the area in (b), and (g) is the F element distribution map corresponding to the area in (b).

[0029] Figure 6 NBF-NiS / Mo in Example 1 of the present invention 2 CT x EPR spectrum.

[0030] Figure 7 NBF-NiS / Mo in Example 1 of the present invention 2 CT x Nitrogen adsorption-desorption isotherms.

[0031] Figure 8 (a) is the NBF-NiS / Mo in Example 1 of the present invention 2 CT x , NiS / Mo in Comparative Example 1 2 CT x , the polarization curve of NBF-NiS in comparative example 2; (b) the polarization curve of NBF-NiS / Mo in embodiment 1 of the present invention 2 CT x , NiS / Mo in Comparative Example 1 2 CT x, the Tafel curve of NBF-NiS in comparative example 2; (c) the Tafel curve of NBF-NiS / Mo in example 1 of the present invention 2 CT x (d) is the chronopotentiometry curve of NBF-NiS / Mo in Example 1 of the present invention. 2 CT x , NiS / Mo in Comparative Example 1 2 CT x , Nyquist plot of NBF-NiS in Comparative Example 2.

[0032] Fig. 9 (a) is the NBF-NiS / Mo in Example 1 of the present invention 2 CT x Cyclic voltammetry curve of NiS / Mo in Comparative Example 1; (b) 2 CT x (c) is the cyclic voltammetry curve of NBF-NiS in comparative example 2 of the present invention; (d) is the cyclic voltammetry curve of NBF-NiS / Mo in example 1 of the present invention 2 CT x , NiS / Mo in Comparative Example 1 2 CT x , C of NBF-NiS in Comparative Example 2 dI Value test result graph. DETAILED DESCRIPTION

[0033] The present invention provides a metal sulfide-based composite catalyst and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0034] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0035] For HER, the best catalyst is the precious metal Pt, but its large-scale application is restricted by its high price and production cost. Transition metal sulfide catalysts have a lamellar structure similar to graphene and belong to the hexagonal crystal system. They have the advantages of low price, sufficient raw materials, good corrosion resistance, and good catalytic performance. They are excellent hydrogen production catalysts, so they are often used as raw materials for electrocatalysts in the field of electrocatalysis. Compared with other transition metal compounds, transition metal sulfides have unique catalytic active centers, which allows the metal ions to pair with the lone pair of electrons on the oxygen of the hydroxide during the reaction, while sulfur attracts protons with the lone pair of electrons, which increases the rate of the hydrogen evolution reaction and is conducive to the reaction. Although the transition metal sulfide catalyst with a lamellar structure has active edge sites with high electrocatalytic activity and fast electrochemical response, its electronic conductivity has anisotropic behavior, that is, the electron transfer on the nanosheet base is slow, and its conductivity still needs to be improved, and the reaction activity on the active sites of the transition metal sulfide catalyst with a lamellar structure is insufficient, which greatly limits the HER performance of the transition metal sulfide catalyst. Based on this, an embodiment of the present invention provides a metal sulfide-based composite catalyst, wherein the metal sulfide-based composite catalyst includes a MXene substrate and a nickel sulfide nanosheet doped with non-metal atoms containing sulfur vacancies loaded on the surface of the MXene substrate.

[0036] In this embodiment, the metal sulfide-based composite catalyst includes a MXene substrate and a nickel sulfide nanosheet doped with non-metallic atoms containing sulfur vacancies loaded on the surface of the MXene substrate. Nickel sulfide nanosheets have high stability and corrosion resistance, and have a d electronic structure similar to that of Pt, and can play an excellent catalytic performance in the hydrogen evolution reaction. The nickel sulfide nanosheets are doped with non-metallic atoms to cause lattice distortion, and then sulfur vacancies can be introduced to enhance the ability to capture protons and enhance the reaction activity. At the same time, the nickel sulfide nanosheets are doped with non-metallic atoms to increase the number of active sites and improve the conductivity; the sulfur vacancies in the nickel sulfide nanosheets can serve as additional active sites for the hydrogen evolution reaction, and at the same time, the electrons are positioned near the defects, which is conducive to the transfer of electrons to proton hydrogen, thereby greatly improving the catalytic performance. Since MXene materials have a two-dimensional layered structure and excellent metallic conductivity, the specific surface area and conductivity of the composite catalyst can be further improved by introducing MXene materials, accelerating the transmission of electrons, and there is a synergistic coupling effect between the nickel sulfide nanosheets doped with non-metallic atoms and the MXene materials, which can adjust the electronic structure of the intermediates in the catalytic hydrogen evolution reaction process, reduce its energy barrier, and improve the hydrogen evolution reaction performance. The metal sulfide-based composite catalyst provided by the present invention has abundant sulfur vacancies, a large electrochemically active specific surface area, a high double-layer capacitance, a low Tafel slope, a large number of active sites, and excellent electrocatalytic activity.

[0037] In one embodiment, non-metal atom-doped nickel sulfide nanosheets are loaded on the surface of a MXene substrate, and the surface of the MXene substrate is completely or partially wrapped by the non-metal atom-doped nickel sulfide nanosheets. There is a certain angle between the non-metal atom-doped rhenium disulfide nanosheets and the MXene nanosheets, that is, the non-metal atom-doped rhenium disulfide nanosheets and the MXene nanosheets are not in a parallel position relationship, for example, the non-metal atom-doped rhenium disulfide nanosheets can be loaded vertically on the surface of the MXene nanosheets.

[0038] In one embodiment, the non-metal atom is selected from one or more of N atom, B atom, and F atom, but is not limited thereto.

[0039] In one embodiment, the non-metallic atoms are selected from N atoms, B atoms and F atoms. In this embodiment, the nickel sulfide nanosheets are co-doped with N atoms, B atoms and F atoms to cause lattice distortion, thereby introducing sulfur vacancies to enhance the ability to capture protons and enhance the reaction activity. At the same time, the co-doping of N atoms, B atoms and F atoms can increase the number of active sites, improve electrical conductivity, and further enhance its ability to capture protons.

[0040] In one embodiment, the mass ratio of the MXene substrate to the nickel sulfide nanosheets doped with non-metallic atoms containing sulfur vacancies is 1:(3-5), for example, 1:3, 1:4 or 1:5, etc. This ratio can better exert the synergistic coupling effect between the nickel sulfide nanosheets doped with non-metallic atoms containing sulfur vacancies and the MXene material.

[0041] In one embodiment, the MXene substrate is selected from Mo 2 CT x Substrate, Ti 3 C 2 T x Substrate, Ti 2 CT x Base, Cr 2 CT x Base and V 2 CT xOne or more of the substrate, wherein T represents a functional group and x represents the number of functional groups. Since the MXene material is a layered material formed by extracting the A layer from the MAX material by a chemical stripping method, functional groups are introduced during the preparation process. The functional group can be a hydroxyl group, an oxygen ion, an acid radical ion, and the like. For example, when the MAX material is corroded by HF acid, fluoride ions exist among the functional groups. MXene materials are similar to general carbon materials and have very high electrical conductivity, but the specific surface area of ​​MXene materials is larger, and the molecular structure can be adjusted through different synthesis schemes, and the oxidation resistance and hydrophilicity are also more outstanding. The present invention can further improve the specific surface area and conductivity of the composite catalyst by introducing MXene materials, accelerate the transmission of electrons, and there is a synergistic coupling effect between the nickel sulfide nanosheets doped with non-metallic atoms and the MXene materials, which can adjust the electronic structure of the intermediates in the catalytic hydrogen evolution reaction, reduce their energy barriers, and improve the hydrogen evolution reaction performance. Specifically, the nickel sulfide nanosheets doped with non-metallic atoms containing sulfur vacancies are loaded on the MXene substrate, and there is a strong interface interaction between the two, resulting in charge transfer between the two, changing the original electronic structure and producing a synergistic coupling effect. Therefore, compared with the nickel sulfide nanosheets or MXene substrates, the metal sulfide-based composite catalyst has a lower energy barrier for hydrogen adsorption, thereby promoting the hydrogen evolution reaction.

[0042] The present invention also provides a method for preparing the metal sulfide-based composite catalyst as described above, which comprises the steps of:

[0043] S1. Adding MXene, nickel salt, urea, citric acid, and an ionic liquid containing non-metal atoms into water to obtain a mixed solution;

[0044] S2, reacting the mixed solution at a temperature of 120 to 160° C. for 8 to 16 hours;

[0045] S3, subjecting the product obtained after the reaction to a sulfurization treatment to obtain the metal sulfide-based composite catalyst.

[0046] In this embodiment, MXene is used as a substrate, and nickel salt, urea, citric acid, and ionic liquid containing non-metallic atoms are used as reactants to prepare a non-metallic atom-doped Ni double-layer hydroxide (LDH) containing sulfur vacancies on a MXene substrate by a hydrothermal method, and then a non-metallic atom-doped nickel sulfide nanosheet containing sulfur vacancies is obtained after sulfidation treatment. Among them, the ionic liquid provides non-metallic atoms, the nickel salt is used as a nickel source, and urea and citric acid are used as ligands of Ni ions to generate an intermediate product, Ni double-layer hydroxide (LDH). The preparation method in this embodiment is simple and low in cost.

[0047] In step S1, in one embodiment, the MXene is selected from Mo 2 CT x 、Ti 3 C 2 T x 、Ti 2 CT x Cr 2 CT x and V 2 CT x One or more of, but not limited to. 2 T x As an example, the preparation method is introduced. 2 CT x The nanosheets were synthesized from bulk Mo by HF 2 Ga 2 C is synthesized by selectively etching the Ga layer. 2 Ga 2 C powder was added to HF solution and stirred for a period of time to allow it to react fully. After centrifugation, the product Mo was obtained. 2 CT x .

[0048] In one embodiment, the nickel salt is selected from at least one of nickel nitrate, nickel chloride, and nickel acetate, but is not limited thereto.

[0049] In one embodiment, the ionic liquid containing non-metal atoms is selected from at least one of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-fluoropyridine tetrafluoroborate, and tri-n-butylphosphine tetrafluoroborate, but is not limited thereto.

[0050] In step S2, nickel salt, urea, citric acid, and ionic liquid containing non-metallic atoms undergo hydrothermal reaction to generate Ni double-layer hydroxide doped with non-metallic atoms and grow uniformly on the surface of the MXene substrate. In other words, during the reaction, Ni double-layer hydroxide doped with non-metallic atoms is generated and grows on the surface of the MXene substrate to form nanosheets, which are finally fully or partially wrapped on the MXene surface, thereby achieving the loading of nickel sulfide nanosheets doped with non-metallic atoms on the surface of the MXene substrate.

[0051] In step S3, the MXene substrate with non-metal atom-doped Ni double-layer hydroxide on the surface is subjected to a sulfidation treatment, so that the non-metal atom-doped Ni double-layer hydroxide therein is converted into non-metal atom-doped nickel sulfide nanosheets.

[0052] In one embodiment, the temperature of the vulcanization treatment is 450-550°C, and the time is 50-70 minutes. For example, the temperature of the vulcanization treatment is 450°C, 480°C, 500°C, 520°C or 550°C, and the time is 50 minutes, 55 minutes, 60 minutes, 65 minutes or 70 minutes.

[0053] In one embodiment, the step of subjecting the product obtained after the reaction to a sulfurization treatment specifically comprises:

[0054] The product obtained after the reaction and the sulfur powder are placed at different positions of the sintering furnace and heated respectively, and the product after the reaction is subjected to a sulfurization treatment.

[0055] The present invention also provides an application of the metal sulfide-based composite catalyst described in the present invention in an electrocatalytic hydrogen evolution reaction. The present invention also provides an application of the metal sulfide-based composite catalyst prepared by the preparation method described in the present invention in an electrocatalytic hydrogen evolution reaction.

[0056] The following describes it in detail through specific embodiments.

[0057] Example 1

[0058] Will 2g Mo 2 Ga 2 The C powder was ground for 30 min, then slowly added to 20 mL of HF solution and placed on a magnetic stirring heating sleeve at 55 °C for 7 days. Then, the Mo was obtained by centrifugation at 10,000 rpm for 10 min. 2 CT x , wash Mo with deionized water 2 CT x Several times until the pH value of the solution reaches about 6. Finally, the obtained Mo 2 CT x The powder was dried in a freeze dryer. 2 CT x The SEM images are as follows Figure 1 As shown in (a), it can be seen from the figure that Mo 2 CT x It is a two-dimensional sheet structure. 2 CT x The XRD pattern of Figure 3 shown.

[0059] 0.55 g nickel nitrate, 0.75 g urea, 0.05 g citric acid, 0.33 mL 1-vinyl-3-ethylimidazolium tetrafluoroborate, 20 mg Mo 2 CT x, 30 mL of ultrapure water were added into the reactor, placed in an ultrasonic cleaner and stirred evenly with a glass rod, and then placed in a constant temperature box at 120°C for 10 hours.

[0060] The product after the reaction was taken out and washed three times with a centrifuge (7800 rpm / min, 3 min each time), and then dried in an oven. The obtained product was recorded as NBF-Ni-LDH / Mo 2 CT x NBF-Ni-LDH / Mo 2 CT x The SEM images are as follows Figure 1 As shown in (b), it can be seen from the figure that NBF-Ni-LDH nanosheets are loaded on Mo 2 CT x surface.

[0061] Put NBF-Ni-LDH / Mo 2 CT x Pour into a quartz boat, add 500 mg of sulfur powder into another quartz boat, then put the two quartz boats into a sintering furnace for sulfurization treatment, set the heating time to 94 min, the temperature to 500 ° C, the insulation time to 60 min, and after cooling, obtain a metal sulfide-based composite catalyst, recorded as NBF-NiS / Mo 2 CT x NBF-NiS / Mo 2 CT x The SEM images are as follows Figure 1 As shown in (c), it can be seen from the figure that NBF-NiS nanosheets are loaded on Mo 2 CT x Surface; NBF-NiS / Mo 2 CT x The TEM image is as follows Figure 2 As shown in (a) and (b), Figure 2 In (b), it can be seen that the lattice fringe spacing of NiS (101) crystal plane is 0.259nm; NBF-NiS / Mo 2 CT x The XRD pattern of Figure 3 Shown; NBF-NiS / Mo 2 CT x The XPS test results are as follows Figure 4 As shown, Figure 4 (a) is the 1s characteristic peak spectrum of B. Figure 4 (b) is the 1s characteristic peak spectrum of N. Figure 4 (c) is the 1s characteristic peak spectrum of F. Figure 4 (d) is the 3d characteristic peak spectrum of Mo. Figure 4 (e) is the 1s characteristic peak spectrum of C. Figure 4 (f) is the 2p characteristic peak spectrum of Ni, Figure 4 (g) is the 2p characteristic peak spectrum of S, confirming the doping of B, N, and F. NBF-NiS / Mo 2 CT x EDS test such as Figure 5 As shown, Figure 5 (a) is NBF-NiS / Mo 2 CT x The element content results in Figure 5 (c)-(g) are the element distribution maps obtained when the corresponding SEM scans in (b) are performed, (c) is the distribution map of the Ni element, (d) is the distribution map of the S element, (e) is the distribution map of the B element, (f) is the distribution map of the N element, and (g) is the distribution map of the F element, which further confirms the doping of B, N, and F.

[0062] For NBF-NiS / Mo 2 CT x EPR was performed and the results were as follows Figure 6 As shown, the EPR spectrum confirms the existence of sulfur vacancies. The use of ionic liquids can achieve N, B, and F doping and introduce sulfur vacancies into N, B, and F-doped NiS nanosheets.

[0063] NBF-NiS / Mo 2 CT x The nitrogen adsorption-desorption isotherm is as follows Figure 7 As shown, its specific surface area is 28.8m 2 ·g -1 .

[0064] Comparative Example 1

[0065] Will 2g Mo 2 Ga 2 The C powder was ground for 30 min, then slowly added to 20 mL of HF solution and placed on a magnetic stirring heating sleeve at 55 °C for 7 days. Then, the Mo was obtained by centrifugation at 10,000 rpm for 10 min. 2 CT x , wash Mo with deionized water 2 CT x Several times until the pH value of the solution reaches about 6. Finally, the obtained Mo 2 CT x The powder was dried in a freeze dryer.

[0066] 0.55g nickel nitrate, 0.75g urea, 0.05g citric acid, 20mg Mo 2 CT x, 30 mL of ultrapure water were added into the reactor, placed in an ultrasonic cleaner and stirred evenly with a glass rod, and then placed in a constant temperature box at 120°C for 10 hours.

[0067] The product after the reaction was taken out and washed three times with a centrifuge (7800 rpm / min, 3 min each time), and then dried in an oven. The obtained product was recorded as Ni-LDH / Mo 2 CT x .

[0068] Ni-LDH / Mo 2 CT x Pour into a quartz boat, add 500 mg of sulfur powder into another quartz boat, then put the two quartz boats into a sintering furnace for sulfurization treatment, set the heating time to 94 min, the temperature to 500 ° C, the insulation time to 60 min, and after cooling, obtain a metal sulfide-based composite catalyst, recorded as NiS / Mo 2 CT x .

[0069] Comparative Example 2

[0070] 0.55 g of nickel nitrate, 0.75 g of urea, 0.05 g of citric acid, 0.33 mL of 1-vinyl-3-ethylimidazole tetrafluoroborate, and 30 mL of ultrapure water were added to a reaction kettle, placed in an ultrasonic cleaner and stirred evenly with a glass rod, and then placed in a constant temperature box at 120° C. for reaction for 10 hours.

[0071] The product after the reaction was taken out and washed three times with a centrifuge (7800 rpm / min, 3 min each time), and then placed in an oven for drying. The obtained product was recorded as NBF-Ni-LDH.

[0072] Pour NBF-Ni-LDH into a quartz boat, add 500 mg of sulfur powder into another quartz boat, and then put the two quartz boats into a sintering furnace for sulfurization treatment. Set the heating time to 94 min, the temperature to 500 °C, and the insulation time to 60 min. After cooling, a metal sulfide-based composite catalyst is obtained, which is recorded as NBF-NiS.

[0073] The NBF-NiS / Mo in Example 1 2 CT x , NiS / Mo in Comparative Example 1 2 CT x , the NBF-NiS in Comparative Example 2 was made into a working electrode, and 2 SO 4 Electrochemical performance test in electrolyte:

[0074] (1) Polarization curve diagram Figure 8As shown in (a), it can be seen from the figure that NBF-NiS / Mo 2 CT x It has the lowest overpotential, the highest current density, and the highest hydrogen evolution activity. NBF-NiS / Mo 2 CT x With NiS / Mo 2 CT x By comparison, it can be seen that doping with N, B, and F atoms can improve the hydrogen evolution activity of the catalyst.

[0075] (2) Tafel curve Figure 8 As shown in (b), it can be seen from the figure that NBF-NiS / Mo 2 CT x Has the lowest Tafel slope of 68.9mV / dec, NiS / Mo 2 CT x The Tafel slope of is 75.5mV / dec, and the Tafel slope of NBF-NiS is 82.7mV / dec.

[0076] (3)NBF-NiS / Mo 2 CT x The chronopotentiometry curve is as follows Figure 8 As shown in (c), the current density is kept at -10 mA cm -2 .

[0077] (4) Nyquist diagram Figure 8 As shown in (d), it can be seen that NBF-NiS / Mo 2 CT x The polarization internal resistance is the smallest.

[0078] (5) Cyclic voltammetry curves are shown in Fig. 9 As shown in (a)-(c), NBF-NiS / Mo 2 CT x With NiS / Mo 2 CT x and NBF-NiS with better cyclic voltammetric characteristics.

[0079] (6)C dI Value Fig. 9 As shown in (d), NBF-NiS / Mo 2 CT x With the highest C dI The value is 2.59mF·cm -2 ,NiS / Mo 2 CT x C dI The value is 1.24mF·cm -2 , NBF-NiS CdI The value is 0.58mF·cm -2 .

[0080] In summary, the present invention provides a metal sulfide-based composite catalyst and a preparation method and application thereof, wherein the metal sulfide-based composite catalyst comprises a MXene substrate and a nickel sulfide nanosheet doped with non-metallic atoms containing sulfur vacancies loaded on the surface of the MXene substrate. The nickel sulfide nanosheet has high stability and corrosion resistance, and has a d electronic structure similar to that of Pt, and can play an excellent catalytic performance in the hydrogen evolution reaction. The nickel sulfide nanosheet is doped with non-metallic atoms to cause lattice distortion, thereby introducing sulfur vacancies to enhance the ability to capture protons and enhance the reaction activity. At the same time, the nickel sulfide nanosheet is doped with non-metallic atoms to increase the number of active sites and improve the conductivity; the sulfur vacancies in the nickel sulfide nanosheet can be used as additional active sites for the hydrogen evolution reaction, and at the same time, the electrons are positioned near the defects, which is conducive to the transfer of electrons to proton hydrogen, thereby greatly improving the catalytic performance. Since MXene materials have a two-dimensional layered structure and excellent metallic conductivity, the specific surface area and conductivity of the composite catalyst can be further improved by introducing MXene materials, accelerating the transmission of electrons, and there is a synergistic coupling effect between the nickel sulfide nanosheets doped with non-metallic atoms and the MXene materials, which can adjust the electronic structure of the intermediates in the catalytic hydrogen evolution reaction process, reduce its energy barrier, and improve the hydrogen evolution reaction performance. The metal sulfide-based composite catalyst provided by the present invention has abundant sulfur vacancies, a large electrochemically active specific surface area, a high double-layer capacitance, a low Tafel slope, a large number of active sites, and excellent electrocatalytic activity.

[0081] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A metal sulfide-based composite catalyst, characterized in that: The metal sulfide-based composite catalyst comprises a MXene substrate and nickel sulfide nanosheets doped with non-metal atoms containing sulfur vacancies and supported on the surface of the MXene substrate; The non-metal atom is selected from one or more of N atom, B atom and F atom; The preparation method of the metal sulfide-based composite catalyst comprises the steps of: Adding MXene, nickel salt, urea, citric acid, and an ionic liquid containing non-metal atoms into water to obtain a mixed solution; The mixed solution is reacted at a temperature of 120 to 160° C. for 8 to 16 hours; The product obtained after the reaction is subjected to a sulfurization treatment to obtain the metal sulfide-based composite catalyst; The ionic liquid containing non-metal atoms is selected from at least one of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-fluoropyridine tetrafluoroborate and tri-n-butylphosphine tetrafluoroborate.

2. The metal sulfide-based composite catalyst according to claim 1, characterized in that The MXene substrate is selected from Mo2CT x Substrate, Ti3C2T x Substrate, Ti2CT x Substrate, Cr2CT x Substrate, V2CT x One or more of the substrates, wherein T represents a functional group and x represents the number of functional groups.

3. The metal sulfide-based composite catalyst according to claim 1, characterized in that: The mass ratio of the MXene substrate to the nickel sulfide nanosheets doped with non-metal atoms containing sulfur vacancies is 1:(3-5).

4. A method for preparing a metal sulfide-based composite catalyst according to any one of claims 1 to 3, characterized in that: Includes steps: Adding MXene, nickel salt, urea, citric acid, and an ionic liquid containing non-metal atoms into water to obtain a mixed solution; The mixed solution is reacted at a temperature of 120 to 160° C. for 8 to 16 hours; The product obtained after the reaction is subjected to a sulfurization treatment to obtain the metal sulfide-based composite catalyst; The ionic liquid containing non-metal atoms is selected from at least one of 1-vinyl-3-ethylimidazolium tetrafluoroborate, 1-fluoropyridine tetrafluoroborate and tri-n-butylphosphine tetrafluoroborate.

5. The preparation method according to claim 4, characterized in that: The nickel salt is selected from at least one of nickel nitrate, nickel chloride and nickel acetate.

6. The preparation method according to claim 4, characterized in that: The temperature of the vulcanization treatment is 450-550° C. and the time is 50-70 minutes.

7. The preparation method according to claim 4, characterized in that: The step of subjecting the product obtained after the reaction to a sulfurization treatment specifically comprises: The product obtained after the reaction and the sulfur powder are placed at different positions of the sintering furnace and heated respectively, and the product after the reaction is subjected to a sulfurization treatment.

8. Use of the metal sulfide-based composite catalyst according to any one of claims 1 to 3 in an electrocatalytic hydrogen evolution reaction; Alternatively, use of a metal sulfide-based composite catalyst prepared by the preparation method according to any one of claims 4 to 7 in an electrocatalytic hydrogen evolution reaction.

Citation Information

Patent Citations

  • Composite catalyst, preparation method and application thereof

    CN113481528A

  • Monatomic site catalyst and preparation method thereof

    CN116200771A